2015
DOI: 10.1523/jneurosci.0261-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Periaqueductal Gray Orchestrates Sensory and Motor Circuits at Multiple Levels of the Neuraxis

Abstract: The periaqueductal gray (PAG) coordinates behaviors essential to survival, including striking changes in movement and posture (e.g., escape behaviors in response to noxious stimuli vs freezing in response to fear-evoking stimuli). However, the neural circuits underlying the expression of these behaviors remain poorly understood. We demonstrate in vivo in rats that activation of the ventrolateral PAG (vlPAG) affects motor systems at multiple levels of the neuraxis through the following: (1) differential control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 71 publications
4
57
0
1
Order By: Relevance
“…Thus, in the subcortical auditory network, the activity of the only previously identified ROI (SOC) was unchanged in the Flx+Sz group as compared to the Sal+Sz+RA group, suggesting that fluoxetine's effects on this structure are not critical for S-IRA block. 5,[22][23][24][39][40][41] The significant decrease in PAG activity seen in the DBA/1 mice that exhibited S-IRA (Sal+Sz+RA) when compared to the mice not subjected to seizure (Sal-noSz) strongly suggests that activation of the PAG did not occur in response to the apnea that resulted in S-IRA. 37 In the SML network, the amygdala, PAG, and RF ROIs showed significant increases in activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in the subcortical auditory network, the activity of the only previously identified ROI (SOC) was unchanged in the Flx+Sz group as compared to the Sal+Sz+RA group, suggesting that fluoxetine's effects on this structure are not critical for S-IRA block. 5,[22][23][24][39][40][41] The significant decrease in PAG activity seen in the DBA/1 mice that exhibited S-IRA (Sal+Sz+RA) when compared to the mice not subjected to seizure (Sal-noSz) strongly suggests that activation of the PAG did not occur in response to the apnea that resulted in S-IRA. 37 In the SML network, the amygdala, PAG, and RF ROIs showed significant increases in activity.…”
Section: Discussionmentioning
confidence: 99%
“…These mice also show spontaneous absencelike seizures accompanied by spike-wave discharges on the electroenceophalogram. [22][23][24] Evidence for the involvement of specific brainstem structures, including the PAG, as regions of interest (ROIs) in seizure-induced death in DBA/1 mice has also been observed in a manganese-enhanced magnetic resonance neuroimaging (MEMRI) study. 8,10,15,16 Neuroimaging studies have observed pathological changes in brainstem structures, including the periaqueductal gray (PAG), in patients who subsequently exhibited SUDEP.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Lack of habituation in amygdalar activity over time suggests a general hyperarousal state in FND. Patients may be more prone than healthy controls to automatic motor defense behavior, such as freeze response, mediated by PAG abnormal activity, because this region is known to be implicated in the freeze response in both animal [65] and human [66,67…”
Section: Physiopathologymentioning
confidence: 99%
“…In this process, however, the synapses that were initially given a low weight may at a later stage of more mature synaptic weight distributions gradually become useful to the system again. Therefore, it is necessary that the parallel fibre synapses on Koutsikou et al (2015). Cerebellar cortical zones are indicated as in Fig.…”
Section: Climbing Fibres Regulate Overall Neuronal Activity and Synapmentioning
confidence: 99%